Lupus anticoagulant in patients with systemic lupus erythematosus is associated with lower E/A ratio and progressive left ventricular dilatation: a five-year follow-up study. (4th February 2022) - Myhr, KA; Jepsen, MM; Zinglersen, AH; Iversen, KK; Hermansen, MF; Ngo, AT; Pecini, R; Jacobsen, S
Abstract: Funding Acknowledgements: Type of funding sources: Public hospital(s). Main funding source(s): Copenhagen University Hospital Background Systemic lupus erythematosus (SLE) is an autoimmune disease with increased risk of cardiovascular complications such as coronary artery disease, myocarditis, pericarditis and valvular dysfunction. The pathophysiological mechanisms are poorly understood and clinical, biochemical and/or imaging markers to identify high risk patients are warranted. Purpose: We aimed to identify SLE-characteristics that are associated with progressive cardiac dysfunction during a five-year follow-up period in patients with SLE. Methods: A total of 147 patients with SLE were included from 2013 to 2014. All patients underwent standard echocardiography at baseline as well as a collection of blood samples, including a selection of biomarkers. Patients were invited to a five-year follow-up with a total of 108 patients (90 % female, mean age 46 ± 13 years, median disease duration of 14 (7-21) years) completing a full echocardiographic, laboratory, and clinical examination. Multivariate regression analyses with eight independent baseline variables of interest (age, sex, disease activity (SLEDAI-2K), lupus nephritis, ischemic heart disease (IHD), antiphospholipid antibodies (IgM and IgG), and lupus anticoagulant(LAC)) were performed as for the association with baseline echocardiographic parameters as well as for changes during follow-up. Only echocardiographic measurements that changed significantly (p < 0.01) during follow-up were selected for the regression analyses. Left ventricular end-diastolic volume index (LVEDVI) and E/A ratio were log-transformed at baseline in the regression analyses due to non-normality. Results: During a five-year follow-up period, LVEDVI increased from 43.5 ± 13.9 to 52.5 ± 15.7 ml/m2 (p <0.001), and left ventricular diastolic measures declined (E/A ratio 1.4 ± 0.5 vs. 1.3 ± 0.5, p = 0.002; e' velocity 12.8 ± 3.8 vs. 12.0 ± 3.7 ms, p = 0.02; mitral valve deceleration time 227.9 vs. 200.8 ms, p < 0.001), except for E/e' (7.5 ± 3.8 vs. 6.8 ± 3.4, p = 0.02). Left ventricular ejection fraction remained stationary (59.5 ± 6.8 vs. 59.6 ± 6.4 %, p = 0.81). In multivariate regression analyses, presence of LAC was significantly associated with progressive left ventricular dilation during the follow-up period (p = 0.003) but not with higher baseline levels (p = 0.64) (Fig. A1 & A2). LAC was associated with lower E/A ratio at baseline (p = 0.005) but did not predict a decrease of E/A ratio during follow-up (p = 0.24) (Fig. B1 & B2). IHD was associated with higher LVEDVI at baseline (p = 0.004), but not with further progression of dilation (p = 0.07). Conclusion: Presence of LAC was associated with lower E/A ratio at baseline as well as progressive left ventricular dilation during a five-year follow-up period. Hence, LAC might be a predictor of progressive cardiac dysfunction in patients with SLE. LAC is known to have implications for the microvascular circulation, but the clinical significance of the present findings is yet to be elucidated.